2016
DOI: 10.1177/1932296816645121
|View full text |Cite
|
Sign up to set email alerts
|

Registry of Youth Onset Diabetes in India (YDR)

Abstract: This registry provides a unique opportunity to study the natural history of youth-onset diabetes in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
(29 reference statements)
0
28
0
Order By: Relevance
“…18,19 The finding that only 5.2% had T2D in this study is lower than that reported from India (25.8%) and Malaysia (17.7%). 9,10 By contrast, the prevalence of T2D in youth has been reported to be higher than T1D in a study from a tertiary diabetes centre in India (48%) and in Maoris in New Zealand (55%). 20,21 A possible reason for the lower prevalence of T2D in the current study is the presence of undiagnosed patients in the community, as screening for diabetes would usually only occur with the onset of symptoms.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…18,19 The finding that only 5.2% had T2D in this study is lower than that reported from India (25.8%) and Malaysia (17.7%). 9,10 By contrast, the prevalence of T2D in youth has been reported to be higher than T1D in a study from a tertiary diabetes centre in India (48%) and in Maoris in New Zealand (55%). 20,21 A possible reason for the lower prevalence of T2D in the current study is the presence of undiagnosed patients in the community, as screening for diabetes would usually only occur with the onset of symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of the various aetiological types of diabetes found in this study is similar to those reported from India and Malaysia. 9,10 Both the Indian and Malaysian registries showed that most young patients, diagnosed under 25 and 20 years of age respectively, had T1D (63.9% and 71.8%). The SEARCH study in the USA showed a higher prevalence of T1D (1.94/1000) than T2D (0.48/1000) in subjects diagnosed at age < 20 years; but the SEARCH study also showed that the incidence of both T1D and T2D was increasing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations